Malocclusion Traits of Yemeni Female School Children - Al-Zubair, Nabil Muhsen; Almulla, Aussama (Orthodontic Journal of Nepal, 2014)
Objective: To provide detailed information concerning clinically relevant occlusal traits and prevalence of occlusal anomaliesin orthodontically relevant period of dental development. Materials & Method: 1501 Yemeni female school children aged 12 years were clinically examined. Overjet was measured to thenearest of 0.5 mm, and sagittal molar relationship were measured. In addition, missing permanent teeth, crowding, spacing,anterior maxillary and mandibular irregularities and anterior open bite were evaluated. Descriptive analysis was carried out toassess the frequency. Result: 9.1% female presented with at least one missing permanent tooth. The mean overjet was 2.8 mm, an increased overjetgreater than 6 mm was affecting around 4 per cent of the children. Similarly, spacing and crowding were present in 25.8% and30.4% respectively. Anterior open bite was affected in every tenth child. Molar relations other than Class I were reported in 29.5%of the sample. Conclusion: Wide range of orthodontically relevant occlusal traits found in the present study underlines the need for orthodonticscreening of children at the age of 12 years or earlier. DOI: http://dx.doi.org/10.3126/ojn.v4i1.11310 Orthodontic Journal of Nepal Vol.4(1) 2014; 41-44